2009
DOI: 10.1007/s00423-009-0549-x
|View full text |Cite
|
Sign up to set email alerts
|

Drain use after open cholecystectomy: is there a justification?

Abstract: Background Despite randomized trials showing no benefit, drain use after open cholecystectomy continues, perhaps as a result of more complicated patient presentation. We examined the reasons for drain use in patients undergoing open cholecystectomy and evaluated the effect of drain placement on surgical outcomes. Methods Univariate and multivariate analyses compared pre-and intraoperative factors associated with drain placement, and postoperative outcomes in patients undergoing open cholecystectomy at our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The conversion rate to open affects the postoperative complications and the length of stay. Bile spillage was a reason to insert a drain after open cholecystectomy 24 and associated with surgical site infections. 25 Third, the characteristics of included patients were not consistent among studies leading to some heterogeneity in our overall analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion rate to open affects the postoperative complications and the length of stay. Bile spillage was a reason to insert a drain after open cholecystectomy 24 and associated with surgical site infections. 25 Third, the characteristics of included patients were not consistent among studies leading to some heterogeneity in our overall analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, drains in LC are used for the early detection of bile leaks and any unsuspected hemorrhage and to evacuate abdominal fluid collections without the need for more invasive procedures. A large retrospective series reported the following main reasons to insert a drain after open cholecystectomy: (1) operation for cholecystitis, (2) intraoperative bile spillage, and (3) excessive blood loss during the operation [10]. However, experimental studies showed that when a drain is inserted in the peritoneal cavity that contains no fluids, it is quickly surrounded by omentum and completely occluded within 48 h [11].…”
Section: Discussionmentioning
confidence: 99%
“…While it is difficult to find any published data supporting drain use, concerns for infectious source control and a possible biliary leak have been supported in discussion by Schein 14 . However, Zaydfudim et al 17 . could not find a justification for drain placement in cases of excessive intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 While it is difficult to find any published data supporting drain use, concerns for infectious source control and a possible biliary leak have been supported in discussion by Schein. 14 However, Zaydfudim et al 17 could not find a justification for drain placement in cases of excessive intraoperative blood loss. In this study, the use of drains after LC was associated with complicated patient presentations: excessive intraoperative blood loss, difficult operation, and intraoperative bile spillage.…”
Section: Discussionmentioning
confidence: 99%